APPLYING NANOPARTICLES FOR TREATING GIARDIA INFECTION: A SYSTEMATIC REVIEW - ALMOHAMMED, HAMDAN I.; E. ALBALAWI, AISHAH; AL SADOUN, HADEEL; BAKHTIARI, NAVID; AMRAEI, MORTEZA; MOGHADDAM, ALI; LATEEF AL-AWSI, GHAIDAA RAHEEM (International Journal of Applied Pharmaceutics, 2021)
At present, chemotherapy with some drugs such as nitroimidazoes derivatives is the preferred treatment for giardiasis. However, these agents are associated with adverse side effects ranging from nausea to possible genotoxicity. The present investigation was designed to systematically review the in vitro, in vivo, and clinical studies about the efficacy of nanoparticles against giardiasis. The study was carried out based on the 06-PRISMA guideline and registered in the CAMARADES-NC3Rs Preclinical Systematic Review and Meta-analysis Facility (SyRF) database. The search was performed in five English databases, including Scopus, PubMed, Web of Science, EMBASE, and Google Scholar, without time limitation for publications around the world about anti-Giardia effects of all organic and inorganic nanoparticles without date limitation in order to identify all the published articles. The searched words and terms were “Giardiasis”, “Giardia lamblia”, “Giardia intestinalis”, “Giardia duodenalis”, “nanoparticles”, “nanomedicine”, “in vitro”, in vivo”, and “clinical trial”. Out of 312 papers, 10 papers, including 4 in vitro (40.0%), 5 in vivo (50.0%), and 1 in vitro/in vivo (10.0%) up to 2021 met the inclusion criteria for discussion in this systematic review. The most common type of nanoparticles was metal nanoparticles (5 studies, 50.0%) such as silver, gold, etc., followed by organic nanoparticles such as chitosan nanoparticles (4 studies, 40.0%). The results of this review study showed the high efficacy of a wide range of organic and non-organic NPs against giardiasis, indicating that nanoparticles could be considered as an alternative and complementary resource for treating giardiasis, since they have no significant toxicity. However, more studies are required to elucidate this conclusion, especially in clinical systems.